Antibiotic Susceptibility Pattern of Clinical Isolates of Escherichia coli at a Tertiary Care Hospital (KYAMC Journal, 2017)
Infections due to multidrug resistant E.coli range from uncomplicated urinary tract infections to life-threatening sepsis. A retrospective study was conducted to determine the patterns of antimicrobial susceptibility in 173 (12.84%) Escherichia coli strains isolated from 1347 clinical specimens of different types. Isolation and identification of E.coli were done as per routine laboratory protocol directed by Cheesbrough1. The isolation rate of E.coli was 48.57% in stool followed by 17.68% in urine, 25% in wound swabs, and 15.38% in tracheal aspirate etc. Among the 173 isolates 102 (59%) were from males and 71 (41%) were from females. Patients were classified into five age groups: 0-15, 16-30, 31-45, 46-60 and >60 years. E.coli was found highest number in females (13.9%) of age range 31-45 years and in males (22%) belonged to age group of over 60 years. Antimicrobial susceptibility testing by the disk diffusion method was conducted for 22 different antibiotics. The majority of isolated E.coli were highly sensitive to Imipenem (98.18%), Meropenem (97.37%), Amikacin (91.67%), Amoxiclav (80%), Ceftazidime (73.33%), and Gentamycin (71.76%). The antibiotics Tobramycin and Azithromycin were found as moderately sensitive against E.coli with the susceptibility rate of 52.5% and 50% respectively. The isolates show low degree of susceptibility to Penicillin G (9.52%), Carbenicillin (10%), Erythromycin (19.48%), Amoxycillin (19.59%), and Ampicillin (25%). These findings have clinical and epidemiological significance and provide a benchmark for future studies on the pattern of susceptibility of clinical isolates of E.coli in this region as well as may help the clinician to prescribe the right empirical treatment.KYAMC Journal Vol. 7, No.-1, Jul 2016, Page 681-686